‘Essentially no different’ but not the same? an analysis of the rules applicable to the interpretation of double taxation agreements - Hart, Daniel Alan (University of the Witwatersrand, Johannesburg, 2023)
This research report aims to determine whether the rules of interpretation generally applied by South African courts in construing documents are the same as the international rules applicable to the interpretation of double taxation agreements (DTAs). The report will compare the prevailing international law rules regarding the interpretation of treaties with the rules of statutory interpretation applied by South African courts. The goal is to assess whether South African courts should rely on domestic or international law principles when interpreting DTAs, and to this end the report will critically analyse the approach taken in two specific cases, Krok v The Commissioner for the South African Revenue Services 2015 (6) SA 317 (SCA) and ITC 1925 82 SATC 144
A research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2023
Keywords: Double taxation agreements; Interpretation of treaties; international law; UCTD; SDG-8: Decent work and economic growth